Real-world effect of casirivimab and imdevimab cocktail in patients infected with SARS-CoV-2 delta and omicron variants - Rajas Subhash Walinjkar; Maharudra Kumbhar; Rashmi Harihar Shinde; Ekta Chaurasia (Journal of Infection in Developing Countries)
Introduction: The casirivimab and imdevimab antibody cocktail has proven to be extremely effective against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) delta variant. Currently, no data on the clinical outcomes of antibody cocktail with the newer omicron form is available. This retrospective study evaluated the effectiveness of casirivimab and imdevimab antibody cocktail in patients infected with SARS-CoV-2 delta and omicron variants.